ADOPTION OF COCONUT-BASED INTERCROPPING SYSTEMS IN SRI LANKA: THE FALLACY OF CONVENTIONAL WISDOM ON ECONOMIC PROFITABILITY - M.T.N. Fernando; M. E. Daw; I. E. Edward (International Coconut Community, 2000)
Despite the concerted efforts of successive governments in Sri Lanka to popularize coconut-based intercropping (CBI) systems, an intensive land use alternative to traditional less intensive coconut monocropping, its adoption by farmers is as low as 25% of the agronomically potential area of 100,000 ha. Although the adoption of an innovation is influenced by a range of determinants which can be broadly categorized as technical, economic, institutional and personal/social, economic profitability of the technology itself is one of the key determinants influencing its adoption. This study assesses the economics of widely practiced five different CBI systems vis-a-vis coconut monocropping, employing five economic indicators, namely Total Gross Margin (TGM), Net Present Value (NPV), Benefit-Cost Ratio (BCR), returns to labor and returns to capital. Data were collected by a field survey of 113 intercroppers and 37 monocroppers conducted from March to May 1995 in three main coconut growing districts in Sri Lanka, namely: Gampaha; Kurunegala; and, Puttalam. Results revealed that all the CBI systems give higher returns per hectare than coconut monocrops, though some of the indicators, namely BCR and returns to variable costs, are reasonably attractive for monocrop coconuts, albeit they are less than for some CBI systems. The study concluded that the low rate of adoption of CBI systems is not a problem of low profitability. Hence, it is worthwhile to explore the other factors typically influencing the adoption of production technologies to find out the reasons for low adoption of CBI